Combining whole exome sequencing with in silico analysis and clinical data to identify candidate variants in pediatric left ventricular noncompaction. (15th January 2022) - Collyer, John; Xu, Fuyi; Munkhsaikhan, Undral; Alberson, Neely F.; Orgil, Buyan-Ochir; Zhang, Wenying; Czosek, Richard J.; Lu, Lu; Jefferies, John L.; Towbin, Jeffrey A.; Purevjav, Enkhsaikhan
Abstract: Background: Understanding the overall variant burden in pediatric patients with left ventricular noncompaction (LVNC) has clinical implications. Whole exome sequencing (WES) allows detection of coding variants in both candidate cardiomyopathy genes and those included on commercial panels. Other lines of evidence, including in silico analysis, are necessary to reduce the overwhelming number of variants to those most likely having a phenotypic impact. Methods: Five families, including five pediatric probands with LVNC, 5 other affected, and 10 unaffected family members, had WES performed, followed by bioinformatics filtering and Sanger sequencing. Review of the HGMD, variant classification by ACMG guidelines, and clinical information were used to further refine complex genotypes. Results: One nonsense and eleven missense variants were identified. In Family 1, affected siblings carried digenic heterozygous variants: E1350K- MYH7 and A276V- ANKRD1. The proband also carried heterozygous W143X- NRG1 . Four affected members of Family 2 carried K184Q- MYH7 while unaffected members did not. In Family 3, homozygous A161T -MYH7 and heterozygous P4935T- OBSCN variants were identified in the proband with the latter being absent in his unaffected brother. In Family 4, proband's father and half-sibling have mild hypertrabeculation and carry T3796I- PLEC . The proband, carrying T3796I- PLEC and V2878A- OBSCN, demonstrated higher trabeculation burden. The proband in Family 5 carried four variants, R3247W- PLEC, C92Y- ERG, T1233M- NCOR2, and E54K- HIST1H4B . Application of ACMG criteria and clinical data revealed that W143X- NRG1, P4935T- OBSCN, and V2878A- OBSCN likely have no phenotypic role. Conclusions: We report nine variants, including novel T3796I- PLEC and biallelic A161T-MYH7, likely contributing to phenotypes ranging from asymptomatic hypertrabeculation to severe LVNC with heart failure. Highlights: This study uses familial whole exome sequencing, in silico analysis, ACMG variant interpretation, and genotype-phenotype correlation with clinical data to identify novel genetic variants in pediatric left ventricular noncompaction cardiomyopathy (LVNC) with clinical characteristics ranged from asymptomatic hypertrabeculation to infantile presentation and eventual HFrEF necessitating hospitalization. Eleven missense variants and one nonsense variant were confirmed with Sanger sequencing. No reports have been found in the ClinVar database for 7 variants (E1350K- MYH7, W143X- NRG1, P4935T- OBSCN, A161T- MYH7, C92Y- ERG, T1233M- NCOR2, and E54K- HIST1H4B ). This is the first report of missense variants, heterozygous T3796I- PLEC and biallelic A161T -MYH7, causing LVNC. We highlight that variants previously reported as "benign", "likely benign", or "VUS, " according to ACMG, may be clinically significant when identified in combination with others and that MYH7 variants remain a primary driver of disease.